Physical parameters, tensile and compressive strength of dolomite rock samples: influence of grain size - Lakirouhani, Ali; Asemi, Farhad; Zohdi, Afshin; Medzvieckas, Jurgis; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2020)
The purpose of this paper is to investigate the strength, physical and engineering index parameters of selected dolomitic rocks with emphasis on grain size. For this purpose, three groups of dolomite from north western Iran, with the same mineral composition but different grain size, were selected; fine grain, medium grain and coarse grain. Three sets of laboratory experiments are performed on 32 samples: first; petrography tests for determining mineral composition and their percentage, and microstructure of rock containing grain size and grain size distribution, second; experiments to determine the physical properties of the rocks included density, compressional and shear wave velocity, and the third category of experiments included uniaxial compressive strength test, Brazilian tensile strength and point load strength. According to the results; there are significant positive correlation between grain size and uniaxial compressive strength (r = 0.89), point load strength (r = 0.58), Brazilian strength (r = 0.69), and average Young’s modulus (r = 0.64). Also, with increasing grain size, density decreases (r = –0.77). There is strong correlation between compressional wave velocity and shear velocity (r = 0.88). There are also a strong correlation among the uniaxial compressive strength, Brazilian tensile strength and point load strength.